PENGARUH PELATIHAN DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI NEGERI SIPIL DINAS KOPERASI UMKM PROVINSI SULAWESI TENGAH - FRANSISCA, CHARREN (Fakultas Ekonomi Universitas Tadulako, 2019)
This study aims to determine the effect simultaneously, training and work environment on performance; knowing the effect partially, training on performance; knowing the effect partially, the work environment on performance; and knowing the influence of the two independent variables (training and work environment), which are more dominant influence on performance. The population in this study were all employees as many as 77 people. Sampling is done by using a saturated sample (census), that is, the entire population is sampled. The method used in this study is multiple linear regression analysis. The results of this study show that, (1) simultaneously, training and working environment have a significant effect on the performance of the Civil Service Office of Cooperative Central Sulawasi Provincial SMEs; (2) partially, training has a significant effect on the performance of the Civil Servants of the Central UMKM Cooperative Service of the Province of Central Sulawesi; (3) partially, the work environment has a significant effect on the performance of the Civil Servants of the Central UMKM Cooperative Service of the Province of Central Sulawesi; (4) the work environment is more dominant and has a significant effect on the performance of the Civil Servants of the Central UMKM Cooperative Service of the Province of Central Sulawesi.